An intermolecular-split G-quadruplex DNAzyme sensor for dengue virus detection. Issue 55 (7th September 2020) - Ida, Jeunice; Kuzuya, Akinori; Choong, Yee Siew; Lim, Theam Soon
Abstract : Application of split G-quadruplex as DNAzyme reporter system for DNA sensing. Abstract : Nucleic acids have special ability to organize themselves into various non-canonical structures, including a four-stranded DNA structure termed G-quadruplex (G4) that has been utilized for diagnostic and therapeutic applications. Herein, we report the ability of G4 to distinguish dengue virus (DENV) based on its serotypes (DENV-1, DENV-2, DENV-3 and DENV-4) using a split G4-hemin DNAzyme configuration. In this system, two separate G-rich oligonucleotides are brought together upon target DNA strand hybridization to form a three-way junction architecture, allowing the formation of a G4 structure. The G4 formation in complexation with hemin can thus provide a signal readout by generating a DNAzyme that is able to catalyze H2 O2 -mediated oxidation of 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS). This results in a change of color providing a sensing platform for the colorimetric detection of DENV. In our approach, betaine and dimethyl sulfoxide were utilized for better G4 generation by enhancing the target-probe hybridization. In addition to this serotype-specific assay, a multi-probe cocktail assay, which is an all-in-one assay was also examined for DENV detection. The system highlights the potential of split G-quadruplex configurations for the development of DNA-based detection and serotyping systems in the future.